Physicochemical characterization and antioxidant capacity of quinoa progenies from Colombia, Brazil and Ecuador produced in the Brazilian Savanna (2023)
In agroindustry, quinoa is considered a functional food due to its health benefits. However, it is necessary to identify genotypes that have better physicochemical characteristics and high antioxidant capacity for selection in breeding programs. This study aimed to evaluate the physicochemical composition and antioxidant capacity of quinoa genotypes originating from Brazil, Colombia, and Ecuador grown in the Brazilian Savanna (Cerrado) environment. The sowing was carried out at Fazenda Água Limpa, Faculdade de Agronomia e Medicina Veterinária, Universidade de Brasília, located at 15º56' S and 47º55' W, at an altitude of 1,100 m. The physicochemical analysis was performed in 2021 at the Centro de Pesquisa em Alimentação of the Universidade Passo Fundo, Rio Grande do Sul, and the antioxidant capacity analysis was carried out at the Universidad de Santiago de Chile. The moisture, ash, protein, carbohydrates (CHO), crude fiber, lipid, and antioxidant capacity were determined. The original data was submitted to analysis of variance, by the F test (P≤0.05), and the means compared by the Tukey test. Linear correlations (Fischer) (P≤0.01) and (P≤0.05) and hierarchical clustering analysis by the Ward method were performed. The genotypes showed variability in physicochemical characteristics and antioxidant activity. CHO was the major compound present in the seeds, exhibiting an average of 50.16%, the protein average was 15.27%, with the P88 genotype standing out with 16.28%. The lipids, fiber, and ash average content were 3.24, 14.13, 6.0%, respectively. CHO showed a positive correlation with the lipid parameter (r=0.858) and a significant negative correlation with protein (r=-0.785). The Aurora cultivar expressed the highest antioxidant activity (1.96±0.01 mg Trolox/g).